WEB-BASED COMPUTER SALES INFORMATION SYSTEM DESIGN TO IMPROVE TRANSACTION EFFICIENCY AT ONE COMPUTER STORE - Hindun; Irwan; Darmeli Nasution (Bahasa Indonesia, 2026)
One Computer Store, as a provider of computers, laptops, and other supporting devices, still faces challenges in managing sales transactions, such as manual recording processes, limited market reach, and suboptimal sales growth. This situation affects the efficiency of transactions and the store's competitiveness amid increasingly tight business competition. This research aims to design and build a web-based computer sales information system that is capable of increasing transaction efficiency, expanding the market through online sales, and promoting sales growth. The system development method used is the Prototype model, which includes the stages of requirements analysis, system design, implementation, and testing. The system developed provides key features such as product data management, online sales transactions, customer data management, as well as automatic and real-time sales report generation. The results of the study indicate that the web-based information system designed can assist One Computer Store in improving transaction efficiency with faster and more accurate record-keeping, expanding market reach through internet-based access, and supporting increased sales volume. With this system, One Computer Store has a greater opportunity to improve its business competitiveness in digital literacy.